1983
DOI: 10.1271/bbb1961.47.2817
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced complex formation between .KAPPA.-casein and .ALPHA.-lactalbumin.

Abstract: It is considered that heat treatment affects the properties of milk such as heat-stability and chymosin clottability. The heat-induced interaction between K>casein and a-lactalbumin was investigated under various conditions (buffer, pH, ionic strength, temperature). The results obtained, using Sephacryl S-300 gel filtration and sodium dodecylsulfate-polyacrylamide gel electrophoresis, indicated that a complex of the two proteins was formed in 35mMphosphate buffer, pH 7.6, containing 0.4m NaCl on heat treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Although less hydrophobic than WPI at 85 C, it is believed that the higher temperatures resulted in the dissociation of a-LA and b-LG structures leading to reduced hydrodynamic radii. Schokker et al (2000) reported b-LG to be reduced from dimers to monomers at temperatures near 70 C. In addition, although a-LA is reported to denature at relatively low temperatures (64.3 C (Relkin et al, 1993;Boye & Alli, 2000)), at !85 C, free thiol groups are formed (Doi, Tokuyama, Kuo, Ibuki, & Kanamori;Schnack & Klostermeyer, 1980) which makes it highly reactive (BertrandHarb, Baday, Dalgalarrondo, Chobert, & Haertle, 2002;Chaplin & Lyster, 1986;Hong & Creamer, 2002) and prone to aggregation (Livney, Verespej, & Dalgleish, 2003). This combined effect of the reactivity of a-LA and dissociation of b-LG dimers at 85 C and pH 5.0 is suggested to allow for the formation of smaller aggregates.…”
Section: Wpi Aggregationmentioning
confidence: 99%
“…Although less hydrophobic than WPI at 85 C, it is believed that the higher temperatures resulted in the dissociation of a-LA and b-LG structures leading to reduced hydrodynamic radii. Schokker et al (2000) reported b-LG to be reduced from dimers to monomers at temperatures near 70 C. In addition, although a-LA is reported to denature at relatively low temperatures (64.3 C (Relkin et al, 1993;Boye & Alli, 2000)), at !85 C, free thiol groups are formed (Doi, Tokuyama, Kuo, Ibuki, & Kanamori;Schnack & Klostermeyer, 1980) which makes it highly reactive (BertrandHarb, Baday, Dalgalarrondo, Chobert, & Haertle, 2002;Chaplin & Lyster, 1986;Hong & Creamer, 2002) and prone to aggregation (Livney, Verespej, & Dalgleish, 2003). This combined effect of the reactivity of a-LA and dissociation of b-LG dimers at 85 C and pH 5.0 is suggested to allow for the formation of smaller aggregates.…”
Section: Wpi Aggregationmentioning
confidence: 99%
“…Nevertheless, the gels showed increased viscous properties at higher temperatures, perhaps reflecting a decrease in hydrophobic interactions. Doi et al (1983Doi et al ( , 1985 reported the formation of gels upon heating a dispersion mixture of casein and whey proteins. More effective gel formation of heated mixtures of these components was obtained by acidification and re-heating (Doi et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Doi et al (1983Doi et al ( , 1985 reported the formation of gels upon heating a dispersion mixture of casein and whey proteins. More effective gel formation of heated mixtures of these components was obtained by acidification and re-heating (Doi et al, 1985). The casein + WPC gels showed large plastic deformations which may have reflected the existence of large colloidal particles as components of gel network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration increased linearly and peaked at 60 min, where it reached a plateau up to 150 min. There is no indication that they measured the reactive thiol content of the unheated samples but, based on their extrapolation to 0 time, there was an approximately 5-6-fold increase in the thiol concentration up to their plateau value (Doi et al, 1983).…”
Section: Production Of Reactive Thiol Groupsmentioning
confidence: 99%